The new criminal justice thinking - Dolovich, Sharon; Natapoff, Alexandra (Book collections on Project MUSE., 2017)
"After five decades of punitive expansion, the entire U.S. criminal justice system (mass incarceration, the War on Drugs, police practices, the treatment of juveniles and the mentally ill, glaring racial disparity, the death penalty and more) faces challenging questions. What exactly is criminal justice? How much of it is a system of law and how much is a collection of situational social practices? What roles do the Constitution and the Supreme Court play? How do race and gender shape outcomes? How does change happen, and what changes or adaptations should be pursued? The New Criminal Justice Thinking addresses the challenges of this historic moment by asking essential theoretical and practical questions about how the criminal system operates. In this thorough and thoughtful volume, scholars from across the disciplines of legal theory, sociology, criminology, critical race theory, and organizational theory offer crucial insights into how the criminal system works in both theory and practice. By engaging both classic issues and new understandings, this volume offers a comprehensive framework for thinking about the modern justice system"--Publisher's website.